The Effect of Far Right Parties on the Location Choice of Immigrants: Evidence from Lega Nord Mayors - Emanuele Bracco; Maria De Paola; Colin P. Green; Vincenzo Scoppa (Institute of Labor Economics (IZA), 2017)
Immigration has increasingly taken centre-stage in the political landscape. Part of this has been rise in far-right, anti-immigration parties in a range of countries. Existing evidence suggests that the presence of immigrants has a substantial effect on the political views of the electorate, generating an advantage to these parties with anti-immigration or nationalist platforms. This paper explores a closely related but overlooked issue: how immigrant behavior is influenced by these parties. We focus on immigrant location decisions in Northern Italy which has seen the rise of the anti-immigration party Lega Nord. We construct a dataset of mayoral elections in Italy for the years 2002-2014, and calculate the effect of electing a mayor belonging to, or supported by Lega Nord. To identify this relationship we focus on mayors who have been elected with narrow margins of victory in a Regression Discontinuity framework. The election of Lega Nord mayor discourages immigrants from moving into the municipality.
Keywords: J15; J61; D72; 330; immigration; geographical mobility; voting behavior; political economy; regression discontinuity design